2021
DOI: 10.1177/10711007211005781
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes After Total Ankle Replacement With a Novel Fixed-Bearing Implant

Abstract: Background: The Integra Cadence total ankle replacement (TAR) is a fourth-generation anatomic, fixed-bearing implant requiring minimal tibial and talar resection, which has been in clinical use since June 2016. The primary purpose of this study is to assess its short-term clinical and radiographic outcomes after TAR using this prosthesis. Methods: This is a prospective case series of consecutive patients that underwent TAR using this novel fourth-generation prosthesis between June 2016 and November 2017. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 28 publications
7
24
2
Order By: Relevance
“…Few outcome studies on this novel fourth-generation TAA system have been conducted, and these have been limited by industry funding or authorship by inventors. 8,23,32 It is important to evaluate outcomes by independent groups because survivorship may differ between surgeon designers and those not affiliated with implant development. In this non-inventor, non-industry funded study, we found a survivorship of 93.8% and a reoperation rate of 6.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few outcome studies on this novel fourth-generation TAA system have been conducted, and these have been limited by industry funding or authorship by inventors. 8,23,32 It is important to evaluate outcomes by independent groups because survivorship may differ between surgeon designers and those not affiliated with implant development. In this non-inventor, non-industry funded study, we found a survivorship of 93.8% and a reoperation rate of 6.3%.…”
Section: Discussionmentioning
confidence: 99%
“…11 To date, 3 studies have investigated short-term outcomes of this new TAA system, reporting survivorship ranging from 93.7% to 100%, improved patient-reported outcomes, improved coronal alignment, and good postoperative range of motion. 8,23,32 However, all previous reports were either funded or investigated by inventors of the implant, which raises a need for non-industry funded research on this TAA system to support these early clinical and radiographic results.…”
Section: Introductionmentioning
confidence: 99%
“…2 other fixed-bearing designs have been introduced quite recently, the Cadence and the Infinity. For Cadence, short-to mid-term results are promising but studies are few and small (33,34). For Infinity, promising results have been shown in one mid-term study (35); potential problems around the tibial component have, however, been observed (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The prosthesis is characterized by an anatomic-shaped bone-anchored talar component (cobalt chrome alloy) and a polyethylene meniscal insert attached to a bone-anchored tibial component (titanium alloy). 21,29 The articular surface pattern of talar dome is characterized by 2 condylar surfaces. 34 The lateral condyle of the talar dome has a larger radius of curvature compared with the medial condyle of the talar dome.…”
Section: Methodsmentioning
confidence: 99%